Effect of growth hormones under different fertility levels on grain yield and yield attributes of rice (Oryza sativa) - Paraye, P M; Kandalkar, V S; Paliwal, A K; Thakur, S K (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted during wet season of 1991 and 1992 to study the effect of soil and foliar application of growth hormones under different fertility levels on growth and yield of rice (Oryza sativa L.) under lowland condition. Two treatments. viz foliar application of cytokinin (Anand Vishal) at 25 and 50 days after transplanting and soil application of cytokinin with foliar application of triacontanol (Anand Kiran) at 25 and 50 days after transplanting. significantly increased the grains/panicle by 11.2 and 13.5% respectively compared with the control. Foliar application of cytokinin at 25 and 50 days after transplanting also increased the grain yield by 6.53% compared with the control. Application of N 150P44K50.4 significantly increased tne plant height by 4.22%, effective tillers/m2by 9.41 %. grains/panicle by 10.76%, 1000-seed weight by 4.00% and grain yield by 6.88% compared with N 100P26.4K36.6. Â